Systematic Planning and Ecosystem-Based Management as Strategies to Reconcile Mangrove Conservation with Resource Use - Borges, Rebecca; Ferreira, Alexander C.; Lacerda, Luiz D. (Frontiers in Marine Science, 2017)
About 120 million people worldwide live within 10 kilometers of large mangrove forests, and many of them directly depend on the goods and services provided by these ecosystems. However, it remains unclear how to synchronize ecological definitions and legal conservation strategies regarding mangroves, especially in developing countries, such as Brazil. The influence of human populations’ socio-economic context in mangrove conservation policies, as well associated challenges in incorporating this influence, are underestimated or, often, largely ignored. Considering the recent threats emerging from changes in legislation and the lack of spatial and social-ecological integrated data to plan mangroves conservation in Brazil, this paper aims to answer the following questions: 1- What suitable measures could managers and other decision-makers adopt for efficient mangrove conservation planning, having Brazil as a case-study?; 2- What are the site-specific, social-ecological aspects that need to be taken into account when deciding on conservation and management strategies?; and 3- How could science contribute to the development of these measures? In order to achieve an ecosystem-based management approach, mangrove ecosystems should not be divided into sub-systems, but instead treated as an integrated system. Furthermore, interconnections with other coastal ecosystems must be assessed and taken into account. This is crucial for effective systematic conservation planning. Also, most of the particular social-ecological aspects in the different types of mangrove ecosystems along the coast, and how those differences might be considered while planning for conservation, remain poorly understood. Based on similar drivers of change, geological features, and likely impacts of climate change, a macro-unit approach is proposed to group mangrove systems along the Brazilian coast and guide national policies. This paper draws parallels with management approaches worldwide to find common points and hence lessons to be applied in other regional realms. It considers the issues of legal vulnerability and needs for social-ecological data on Brazilian mangroves, contributing towards systematic conservation planning and ecosystem-based management for these ecosystems